Transmission of Soluble and Insoluble α-Synuclein to Mice. Issue 12 (December 2015) - Jones, Daryl Rhys; Delenclos, Marion; Baine, AnnMarie T.; DeTure, Michael; Murray, Melissa E.; Dickson, Dennis W.; McLean, Pamela J.
Abstract : Abstract: The neurodegenerative synucleinopathies, which include Parkinson disease, multiple-system atrophy, and Lewy body disease, are characterized by the presence of abundant neuronal inclusions called Lewy bodies and Lewy neurites. These disorders remain incurable, and a greater understanding of the pathologic processes is needed for effective treatment strategies to be developed. Recent data suggest that pathogenic misfolding of the presynaptic protein, α-synuclein (α-syn), and subsequent aggregation and accumulation are fundamental to the disease process. It is hypothesized that the misfolded isoform is able to induce misfolding of normal endogenous α-syn, much like what occurs in the prion diseases. Recent work highlighting the seeding effect of pathogenic α-syn has largely focused on the detergent-insoluble species of the protein. In this study, we performed intracerebral inoculations of the sarkosyl-insoluble or sarkosyl-soluble fractions of human Lewy body disease brain homogenate and show that both fractions induce CNS pathology in mice at 4 months after injection. Disease-associated deposits accumulated both near and distal to the site of the injection, suggesting a cell-to-cell spread via recruitment of α-syn. These results provide further insight into the prion-like mechanisms of α-syn and suggest that disease-associated α-syn is not homogeneous within a single patient but might exist in both soluble and insoluble isoforms. Abstract : Supplemental digital content is available in the text.